MASKULINITAS DAN KESALEHAN DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL-KHALIEQY - Hidayatullah, Danial; Udasmoro, Wening (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
Identifying the correlation between masculinities and piety in Abidah El-Khalieqy’s Perempuan Berkalung Sorban [A Woman in a Turban] is a way to understand how gender works within a particular culture. As masculinity is not a monolithic concept, the mode of its correlation with piety varies. Based on the analysis of the characters and their characterizations in the novel, it is found that, from the perspective of the female narrator, the practice of piety leads to victimization and oppression of women when it is inscribed with hegemonic masculinity and vice versa. By applying narratology, this research is able to reveal the discursive practices from the combination of masculinities and piety. Khudori is a new kind of character which shares a positive masculinity dreamt by moslem women although his maculinity resembles the non-hegemonic ones. The other kinds of masculinity in this novel that function as a contrast show that the combination of piety and hegemonic masculinity is not desirable. On a structural side, Khudori is created as a part of the structural aspects which serves as a dramatic functionality that fits him best to be a flat character.